High-dose isoniazid in the shorter-course multidrug-resistant tuberculosis regimen in the Republic of Moldova. Issue 4 (12th October 2017) - Chesov, Dumitru; Ciobanu, Nelly; Lange, Christoph; Heyckendorf, Jan; Crudu, Valeriu
Since May 2016 the World Health Organization (WHO) has recommended the treatment of multidrug-resistant tuberculosis (MDR-TB) patients with a standardised treatment regimen of 9–12 months duration if patients fulfil specific eligibility criteria [1]. This shorter-course MDR-TB treatment regimen consists of a combination of seven drugs (clofazimine, ethambutol, high-dose isoniazid, kanamycin, moxifloxacin, prothionamide and pyrazinamide) for 4–6 months, followed by four drugs (moxifloxacin, clofazimine, pyrazinamide and ethambutol) for 5 months. It is based on the results from recent observational cohort studies performed in Bangladesh [2], Cameroon [3] and Niger [4] where this or similar treatment regimens led to high cure rates for MDR-TB. Shortly after the WHO proposed the shorter-course MDR-TB regimen, substantial concerns were raised about the applicability of this regimen for patients with MDR-TB in Europe, where many circulating strains of Mycobacterium tuberculosis have additional resistance to 2nd-line anti-tuberculosis (anti-TB) drugs. Based on results from existing databases with comprehensive records of the drug-susceptibility patterns of M. tuberculosis strains in patients with MDR-TB, several groups reported independently that less than 10% of MDR-TB patients from the WHO European Region were likely to be eligible for this regimen [5–8]. High-dose isoniazid should not be part of a standardised treatment regimen for patients with MDR-TB in Moldova http://ow.ly/zUte30eTtRW